CASE-BASED LEARNING MENINGKATKAN CLINICAL REASONING PADA BLOK PENYAKIT INFEKSI TROPIS MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS ISLAM INDONESIA - Sulistyoningrum, Evy; Lusiyana, Novyan (Jurnal Penelitian Pendidikan, 2018)
Case-based learning (CBL) is a newer modality of teaching healthcare, combining medical theory and practices. Many researchs reported effectivity of CBL to improve student-centered learning. The aim of this study is to evaluate how CBL improved students’ clinical reasoning compared with other method such as problem-based learning. An interventional research involved 4th grade medical students receiving PBL and CBL methods supervised by a tutor or instructure. An alternative method combining CBL and structured role play (in an Integrated-Patient Management method) also performed using clinical scenario with medical practice setting. The result showed that student received CBL had better clinical reasoning indicated from better miniquizz result compared with PBL students (p 0,05, Mann Whitney U test. Students exposed with CBL had final MCQ and essay exam grade compared with unexposed students. Students exposed with CBL also had better clinical skill indicated from Objective Structure Clinical Examination (OSCE) result (p 0,05, independent t test). Students’ acceptance level on CBL method is 79, 4%. It is concluded that compared with PBL, CBL is more effective in improved students’ performance, learning outcomes and clinical reasoning and also had high acceptance among medical students.